Texto e intertextos em Tutaméia (terceiras estórias): uma leitura da linguagem poética de Guimarães Rosa - Ramos, Rita de Cássia (2010)
This work is located in the textual production area and approaches the revealing of implicit meanings in the poetical language of Guimarães Rosa in a short story of Tutaméia (Terceiras Estórias), with the title João Porém, o criador de perus (João Porém, the Turkey Breeder). From a reference system guided by the author, the clues and misleads of the Aletria e hermenêutica foreword, we seek to unveil the secrets of the ingenious enunciation of Guimarães Rosa, which is characterized by the poetical language with which the author creates and recreates lexical units for the linguistic representation of the text. This study is theoretically based on the principles of Critical Discourse Analysis with a social and cognitive branch, of Textual Linguistics, and on studies carried out in relation to the poetical language. Following Jauss (1989), we performed a heuristic, which is linear. Then, we performed the hermeneutic reading, which is non-linear, complemented by inter-texts of a variety of knowledge areas. The findings demonstrate that in the selected short story, the story of João Porém, a back-country dweller that prospers and that brings prosperity to his home county, creates love and remains loyal to a maiden made up by his fellow countrymen, may be defined as belonging to an abstraction. Its purpose is not restricted to entertainment, but to provide learning to readers on the poetical language, which literarily represents the oral mineira variety, on transcendence, with references to platonic reminiscences and in disguise, alluding to the golden years of Brazilian culture